(3YOI GdOGYi hfLGM GdSGYjs - (3CMeO Hf eMeO Hf eMeO Hf agO GdCSOj GdMdj , J (B841 (3g`s
(3ChdgG (B:s
(3GdMeO ddg SGeY GdOYGA hOGaY GdHdGA heajV GdVjGA hcGTa GdXdeGA s
(3BNQgG (B:s
(3hdhdG Efj CcQg GdJWhjd dPcQJ aVd gPG Gdjhe heG CYWi Gddg YR hLd def YQag eG dGojMUi HYOO Je s
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B95s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3GdOcJhQ MSjf Ydj eMahX (B(38) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs